Opportunities and limitations of membrane-based preconcentration for rapid and continuous diagnostic applications. Issue 2 (2nd March 2022) - Drexelius, Amy; Kim, Steve; Hussain, Saber; Heikenfeld, Jason
Abstract : Osmotic or pneumatically-generated pressure gradients can be used in membrane-based filtration processes to preconcentrate biofluid samples for enhanced signal and increased sensitivity in diagnostic sensing applications. Abstract : Modern rapid diagnostic tests have continued to improve in performance and convenience, including the proliferation of point-of-care and the emergence of continuous wearable diagnostics. Frequently, rapid diagnostic tests are challenged in their sensitivity and their limit of detection, especially for disease detection in its early stages where analyte concentration can be lower, leading to false negative test results. In response, preconcentration methods have been explored to increase analyte concentration in the collected sample. In theory, a particularly attractive approach is simple membrane preconcentration, whereby the membrane retains the analyte through size-selective filtration while removing water from the sample. This article reviews two leading methods for membrane-based preconcentration, high-pressure pneumatic and osmotic preconcentration, which have the greatest potential because they can operate with the speed (minutes) required for rapid diagnostic tests. Using these simple yet effective methods, analyte concentration can be rapidly increased by a factor of 100× or more, both in buffer and in biofluids. Data from previous studies and new data found only in this article now allows preliminary conclusions on the benefits and limitations of each method. Preconcentration amounts of 10× were achieved for bovine serum albumin and glucose using osmotic pressure, while preconcentration amounts of >160× were achieved for pregnancy hormone and >70× for flu using pneumatic pressure. While each method is more limited in utility than originally speculated, each method will be shown to have merit for niche applications of both point-of-care and continuous diagnostics, with particular value found in early disease detection.